Distribution and bioprospecting potential of actinobacteria from Indian mangrove ecosystems - Manikkam, Radhakrishnan; Pati, Premalata; Thangavel, Shanmugasundaram; Venugopal, Gopikrishnan; Joseph, Jerrine; Ramasamy, Balagurunathan; Dastager, Syed G. (Microbial Diversity in Ecosystem Sustainability and Biotechnological Applications, 2019)
Actinobacteria are the ecologically and economically important prokaryotes with the unprecedented ability to produce novel metabolites. They are widely distributed in nature due to their physiological and metabolic versatility. Actinobacteria from marine ecosystem are recognized as a promising source for novel bioactive metabolites. Notably, mangroves are the most fertile and productive marine ecosystem due to their ecophysiological conditions and vast microbial diversity. At the global level, there are many novel actinobacteria which have been reported from mangrove ecosystems and also explored for their bioprospecting potential. However, in India, microbiologists have explored actinobacteria from selected mangrove ecosystems for the past five decades with special reference to culturable diversity and antimicrobial, antimycobacterial, anticancer, and enzymatic activities. So far, around 22 rare actinobacterial genera have been reported from the Indian mangrove ecosystems. However, several other novel actinobacteria with promising bioprospecting potential are yet to be explored. Hence, research on actinobacteria in the Indian mangrove ecosystem is still in its infancy. This chapter will describe the exploratory research work carried out on the importance, diversity, antimicrobial and enzymatic activity, biodegradation, and nanotechnological potency of actinobacteria from the Indian mangrove ecosystems. This chapter will enable researchers to identify the gaps to be bridged for further research on Indian mangrove actinobacteria and exploit their potential to the maximum benefit to mankind.